Nonlinear Behavior of Space Trusses Considering Initial Imperfection - หะยียูโซะ, อิมรอน; สมิทธากร, วัฒนชัย (Princess of Naradhiwas University Journal, 2018)
Construction in civil work has found many problems. One of them is the imperfection of the structure which is inevitable. This will affect behavior of structure both nonlinear geometric and nonlinear material and will make structure unstable leading to decreasing in the capacity of structure. This research presents a simulation of loading behavior of space truss using both nonlinear geometric analysis and nonlinear material analysis. In addition, the imperfection in cases out-of-straightness and out-of-plumbness were considered. The analysis result showed that the capacity of some type of space truss are very sensitive to the initial imperfection. As a result, the structure will deform to its unstable condition more rapidly.